2018
DOI: 10.1155/2018/9410560
|View full text |Cite
|
Sign up to set email alerts
|

Recent Investigations of Phase Change Materials Use in Solar Thermal Energy Storage System

Abstract: Solar thermal energy storage (TES) is an efficient way to solve the conflict between unsteady input energy and steady output energy in concentrating solar power plant. The latent heat thermal energy storage (LHTES) system is a main method of storing thermal energy using phase change materials (PCMs). Thermal properties, that is, melting points and latent heat, are the key parameters of PCMs for the TES system. In this paper, the PCMs are classified into inorganic and organic by the chemical composition, and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 118 publications
0
8
0
Order By: Relevance
“…High-temperature solar energy plants (temperature above 300°C), in particular have attracted the attention of researchers world-wide. Inorganic salts as PCMs can effectively store the energy at high temperatures due to their capacity to produce large amount of latent heat with minimal change in density during phase change form solid to liquid [45].…”
Section: Pcms For Storage Of Solar Energymentioning
confidence: 99%
“…High-temperature solar energy plants (temperature above 300°C), in particular have attracted the attention of researchers world-wide. Inorganic salts as PCMs can effectively store the energy at high temperatures due to their capacity to produce large amount of latent heat with minimal change in density during phase change form solid to liquid [45].…”
Section: Pcms For Storage Of Solar Energymentioning
confidence: 99%
“…PCMs are classified based on the phase change temperature (lower, higher, and intermediate temperature). Mao et al 4 have classified PCMs, according to melting temperature, into three categories which are low‐temperature materials, medium temperature materials, and high temperature materials, see Figure 2.…”
Section: Phase Change Materialsmentioning
confidence: 99%
“…Mao et al [10] provided an overview of low-temperature PCMs and their latent heat properties. Palomba et al [11] gave an overview of PCMs used in non-concentrating solar applications and identified paraffinic materials and hydrated salts as the most promising solutions.…”
Section: Overview Of Phase Change Materialsmentioning
confidence: 99%